answersLogoWhite

0

Still curious? Ask our experts.

Chat with our AI personalities

JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran
LaoLao
The path is yours to walk; I am only here to hold up a mirror.
Chat with Lao

Add your answer:

Earn +20 pts
Q: What is the answer to 4 5(x 1)2x 3(x 1)?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Math & Arithmetic

5x3-3x plus 4 -3x3-2x2 plus 6x-1?

Am I right :P?5x^(3)-3x+4-3x^(3)-2x+6x-1Since 5x^(3) and -3x^(3) are like terms, add -3x^(3) to 5x^(3) to get 2x^(3).(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=2x^(3)-3x+4-2x+6x-1Since -3x and -2x are like terms, subtract 2x from -3x to get -5x.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=2x^(3)-5x+4+6x-1Since -5x and 6x are like terms, subtract 6x from -5x to get x.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=2x^(3)+x+4-1Subtract 1 from 4 to get 3.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=2x^(3)+x+3To find the derivative of 2x^(3), multiply the base (x) by the exponent (3), then subtract 1 from the exponent.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=6x^(2)+(d)/(dx) x+3To find the derivative of x, multiply the base (x) by the exponent (1), then subtract 1 from the exponent (1-1=0). Since the exponent is now 0, x is eliminated from the term.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=6x^(2)+1+(d)/(dx) 3Since 3 does not contain x, the derivative of 3 is 0.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=6x^(2)+1+0Add 0 to 1 to get 1.(d)/(dx) 5x^(3)-3x+4-3x^(3)-2x+6x-1=6x^(2)+1The derivative of 5x^(3)-3x+4-3x^(3)-2x+6x-1 is 6x^(2)+1.6x^(2)+1


What is the solution to 8x-19 equals 3x plus 1?

8x - 19 = 3x + 1 5x -19 = 1 5x = 20 x = 4


What is 3x to second power over 12x to sixth power in lowest terms?

(3x)2/(12x)6(3x)2=32x2=9x2(12x)6=126x6=2985984x6(3x)2/(12x)6=9x2/2985984x69/2985984=1/331776.x2/x6=x2 * x-6=x-4=1/x4.9x2/2985984x6=1/331776 * 1/x4=1/331776x4


How do you factor 5x2 - 12x 4?

assuming you meant 5x2+12x+4 (5x+2)(x+2)


What is the answer 3x divided 5-x divided 3 equals 4?

3x/(5-x)/3=4 3x/(5-x)=4X3 3x=12(5-x) 3x=60-12x 3x+12x=60 x=4